UPAYA MENINGKATKAN HASIL BELAJAR LOMPAT JAUH GAYA JONGKOK DENGAN BERMAIN LOMPAT DAN LONCAT - Mulyani Mulyani (MEDIA DIDAKTIKA, 2019)
This study aims to determine the improvement of physical education learning in the subject matter of long jump by jumping and jumping. This research design is a classroom action research that lasts two cycles and in each cycle consists of two meetings. The research subjects were class V students of SDN Deketagung, Sugio Subdistrict, Lamongan Regency as many as 19 students. The data of this study were analyzed using quantitative percentage descriptive techniques. The results of this study indicate that there is an increase in classroom learning and long jump skills by jumping and jumping. The class atmosphere is indicated by the activeness of the results from the first cycle to the second cycle of 100% of children in good category (B) and for the development of 95% prefix long jump basic children in the good category (B), 5% of children in the adequate category. Rejection of 95% of children in good category (B), 5% of children in sufficient category (C). As for landing, 89% of children are in good category (B), 11% of children are in the adequate category (C).